Comparative study of clinical efficacy using three-dimensional and two-dimensional laparoscopies in the treatment of distal gastric cancer - Liu, Jungang (Onco Targets Ther, 2018)
BACKGROUND: Three-dimensional (3D) laparoscopy has the advantages and characteristics of more radical procedures in the treatment of gastric cancer. The objective of this research was to investigate the short-term efficacy and safety of 3D laparoscopic procedures in the treatment of advanced distal gastric cancer. METHODS: We retrospectively analyzed the clinical data of 124 patients treated with 3D and two-dimensional (2D) laparoscopic D2 lymphadenectomy for distal gastric cancer at the China Academy of Medical Sciences Cancer Hospital and the Affiliated Cancer Hospital of Guangxi Medical University from January 2014 to January 2015. The effects on operative time, bleeding, hospitalization time, complications, and the number of lymph nodes removed were analyzed. RESULTS: The difference between the general data of the two groups was not statistically significant (P>0.05). In analysis of the subgroups, the number of lymph nodes removed in the 3D laparoscopic group was significantly higher than in the 2D laparoscopic group ([2.52±1.88] vs [2.22±1.80], P=0.001; [2.22±1.80] vs [1.47±1.99], P=0.019). However, the differences among the total number of lymph nodes removed, operative time, intraoperative blood loss, intraoperative complications, postoperative complications, postoperative recovery time, and postoperative hospital stay were not statistically significant. CONCLUSION: 3D laparoscopic-assisted radical gastrectomy for distal advanced gastric cancer is safe and feasible.